THE CONCEPT OF BANCASSURANCE: FORMS, MODELS AND DIRECTIONS FOR ITS IMPLEMENTATION UNDER MODERN CONDITIONS - O. D. Averchenko (Финансы: теория и практика, 2017)
Improving the interaction between banks and insurance companies is necessitated by the need to enhance integration processes to produce competitive products and meet the needs of customers in financial services with a better quality. There is a need to study the principles of bancassurance and analyze the conceptual approaches to the organization and functioning of various forms of integration along with seeking effective models of cooperation. The purpose of the paper is to study different approaches to determining the forms and models of the bancassurance. Effective forms of the bancassurance are proposed using the methods of analysis, logical generalization, scientific abstraction and system-structural analysis.